Mitochondrial Dysfunction and Altered Renal Metabolism in Dahl Salt-Sensitive Rats - Zhengjun Wang; Qiong Sun; Na Sun; Mingyu Liang; Zhongmin Tian (Karger Publishers, 2017)
Background/Aims: The kidney plays a critical role in the control of blood pressure and its elevation in salt-induced hypertension. Mitochondrial dysfunction, especially in energy metabolism, has been associated with hypertension. Here, we aimed to investigate mitochondrial function and metabolic features in renal mitochondria of Dahl salt-sensitive (SS) rats to gain further insight into the relationship between mitochondrial metabolism and predisposition to hypertension. Methods: In this study, SS rats fed low-salt (LS) or high-salt (HS) diets were used to investigate mitochondrial function and metabolism including mitochondrial enzyme activities, pyridine nucleotides, metabolites, and oxidative stress by biochemical analysis and gas chromatography-mass spectrometer (GC-MS). Results: Significantly lower activity levels of fumarase, isocitrate dehydrogenase and succinyl-CoA synthetase were observed in renal mitochondria of SS rats compared with SS.13BN control rats fed LS diets. Intra-mitochondrial pyridine nucleotide content and mitochondrial metabolism were adversely affected in SS rats. In accordance with this, reduced ATP production, Δψm, and superoxide dismutase (SOD) activity were also observed in mitochondria of the renal medulla and cortex of SS rats. Moreover, ATP production was further impaired and oxidative stress was increased, confirming that the mitochondria of SS rats fed HS diets were dysfunctional compared to those of rats fed LS diets. Conclusions: Our data demonstrated that the renal mitochondria of SS rats exhibited complicated metabolic alteration and dysfunction in low-salt diets, and high-salt diets aggravated these dysfunctions. Thus, these results may be associated with renal dysfunction, which, in turn, would help in understanding the development of salt-sensitive hypertension.